Numerical investigation of groundwater flow systems and their evolution due to climate change in the arid Golmud river watershed on the Tibetan Plateau - Xiao, Yong; Liu, Kui; Zhang, Yuqing; Yang, Hongjie; Wang, Shengbin; Qi, Zexue; Hao, Qichen; Wang, Liwei; Luo, Yinfei; Yin, Shiyang (Frontiers in Earth Science, 2022)
Climate warming is the greatest challenges to hydrosphere and human community in future, especially in arid and semiarid regions. This study took Golmud river watershed on Tibetan Plateau as an example to numerically reveal the development of groundwater flow system in large arid sedimentary basin, and explore what would the dramatic climate warming pose on groundwater flow system. The numerical results showed the Golmud river watershed developed three hierarchical groundwater flow systems. River seepage is the predominant recharge for groundwater system inside the basin. The local groundwater flow system discharges some 82.69% of all groundwater in the basin, and is ranked by the intermediate system with 14.26% and the regional system with 3.05%. The local system distributes mainly in the shallow area of the alluvial-pluvial fan at the piedmont and provides the dominant water resource for human exploitation and oasis ecological usages. The climate warming would increase about 30.78% of the recharge water quantity to groundwater system inside the basin via river seepage due to the increasing precipitation and more melted glaciers in the headwater region of the watershed. These waters would pose disturbances on all groundwater flow systems but the degrees are different. The local flow system has the largest responses to the climate warming with more than 90% of increased water cycled in and discharged through this system. The significant groundwater level rising leads to the trailing edge of the overflow belt at the piedmont moving ~5 km towards to the mountain pass, which would potentially pose water disasters to the local region. While the influences of climate warming on intermediate and regional flow system are relatively limited. The study provides preliminary understanding of the climate warming influences on groundwater flow system in arid endorheic basin, and is essential for tackling future climate change challenges facing by arid and semiarid regions.